Osteuropäische Moderne Beiträge jüdischer Architekten und Architektinnen - Gleiter, Jörg H.; Schlusche, Günter; Sonder, Ines (Universitätsverlag der Technischen Universität Berlin, 2022)
The central theme of this publication is the influence of eastern European Jewish architects, who played a significant role in the reform movements in architecture and urban planning early in the 20th century and helped shape modernist architecture, or Neues Bauen. Due to socioeconomic factors, the local architects involved were often Jewish. In German-speaking networks academic institutions as the Bauhaus, the Deutscher Werkbund, and other were quite influential. As in Germany, due to National Socialist persecution, exile or emigration, the architects themselves have frequently been forgotten. 13 scholars and professors from eight eastern European countries and from Israel and Germany reconstruct the interactions and exchanges through the works and biographies of the architects.